Development of novel fermentation systems for the production of nonalcoholic beverages with basidiomycetes - Zhang, Yanyan; Justus Liebig University Giessen (My University, 2015)
Basidiomycetes represent the highest developed class of fungi. They are able to synthesize pharmacological relevant secondary metabolites, natural flavor compounds, and highly sought after enzymes. Because of their biochemical potential, basidiomycetes are ideal tools for the food industry.With the recent worldwide declining consumption of beer, breweries are eagerly searching for innovative nonalcoholic fermented beverages to compensate for this negative trend. Different from microorganisms used in traditional fermented beverages, such as yeasts, lactic acid bacteria, Acetobacter species, and lower fungi, basidiomycetes possess the unique capability of producing a wide range of natural flavors in submerged cultures. Because of the consumers demand for natural food and the above-mentioned biochemical potential, basidiomycetes producing natural flavor compounds are ideal candidates to develop novel fermentation systems for producing nonalcoholic fermented beverages.In novel fermentation systems, 31 edible or medicinal basidiomycetes were cultivated in wort (without hops) for up to 48 h at 24 °C and 150 rpm. Every 2 - 4 h, samples were taken, and species exhibiting interesting flavor impressions were identified with their corresponding fermentation times by sensory evaluation. Afterwards, aroma compounds of the beverages with pleasant flavors were isolated by liquid-liquid extraction (LLE) and by headspace solid phase microextraction (HS-SPME). The key odor-active compounds were analyzed by aroma extract dilution analysis (AEDA) using a gas chromatography system equipped with a tandem mass spectrometry detector and an olfactory detection port (GC-MS/MS-O). For HS-SPME, a revised AEDA method was developed by sequentially increasing the GC inlet split ratio (aroma dilution analysis, ADA). The key odorants of the beverages were analyzed in kinetic studies, quantified, and verified by aroma reconstitution. The biosynthetic pathway of the most important odorant of a beverage fermented by shiitake was elucidated by means of isotopic labeling experiments. The results may help to control and improve the quality of the products in the future.All of the selected basidiomycetes grew well in wort and highly interesting flavor impressions (e.g., green, fruity, floral, honey-like, and toasted) were perceived. Among the 31 screened fungi, shiitake (Lentinula edodes) and Trametes versicolor were rated as the most promising species for producing novel nonalcoholic beverages after sensory evaluation by 10 panelists. The flavors of both beverages were distinctly different from the substrate wort (malty, sweetish, and aromatic).Wort fermented by shiitake exhibited a very pleasant flavor after 48 h, which was perceived as fresh, fruity, plum-like, sweet, and slightly sour. Most of the key odor-active compounds (e.g., 2-acetylpyrrole, ß-damascenone, (E)-2-nonenal, and 2-phenylethanol) were detected with both extraction techniques. However, distinct differences between these two methods were observed. Compounds such as methyl 2-methylbutanoate and (E)-methyl cinnamate, which exhibit typical fruity flavors were only identified by HS-SPME as key odor- active compounds. The kinetic studies indicated that shiitake synthesized fruity and rose-like odors, and simultaneously degraded the typical odorants of the substrate wort during the fermentation. Using the standard addition method, a good linearity and high degree of precision were obtained for the quantification of twelve aroma compounds with flavor dilution (FD) factors ranging from 4 to 64. Methyl 2-methylbutanoate, produced by shiitake, showed the highest odor activity value (OAV 30) and was responsible for the typical fruity odor of the beverage. A correlation between the concentration of methyl 2-methylbutanoate and the perceived fruitiness of the beverage was observed. The biosynthesis of this important methyl ester by transformation of 2-methylbutanoic acid and L-isoleucine was confirmed by means of an isotopic labeling experiment.Another novel beverage fermented by T. versicolor also possessed an appealing aroma profile (fresh, fruity, sweetish, and slightly floral). Six odor-active compounds produced by T. versicolor, ethyl 2-methylbutanoate (OAV 1.2), ethyl 2-methylpropanoate (OAV 31), ß- linalool (OAV 16.4), 2-methylbutanoic acid (OAV 2.0), 3-methylbutanoic acid (OAV 7.0), and 2-methylpropanoic acid (OAV 2.3), were responsible for the overall flavor of the beverage. In addition, the initial oxalic acid concentration of the substrate wort was decreased by 18% during the fermentation with T. versicolor.Shiitake and T. versicolor represent ideal candidates to develop novel fermentation systems to produce nonalcoholic fermented beverages. It is well-known that the sensory and organoleptic characteristics are important for acceptance and utilization of any natural or processed food. In the novel fermentation system, unique flavors were generated in short fermentation times without formation of off-flavors. In addition, the whole fermentation procedures are easy to handle and may be performed with traditional brewery equipment. Shiitake is the second most popular edible mushroom in the global market and was the first medicinal macrofungus to enter the realm of modern biotechnology. T. versicolor has already been recognized as a functional food and promising dietary supplement for promoting health qualities. Therefore, a high consumer acceptance and a high market potential for the novel fermented beverages are expected.
Keywords: ddc:540